From crossbreeding to biotechnology-facilitated improvement of banana and plantain - Ortíz, R.; Swennen, Rony L. (Elsevier, 2014)
The annual harvest of banana and plantain (Musa spp.) is approximately 145 million tons worldwide. About 85% of this global production comes from small plots and kitchen or backyard gardens from the developing world, and only 15% goes to the export trade. Musa acuminata and Musa balbisiana are the ancestors of several hundreds of parthenocarpic Musa diploid and polyploid cultivars, which show multiple origins through inter- and intra-specific hybridizations from these two wild diploid species. Generating hybrids combining host plant resistance to pathogens and pests, short growth cycles and height, high fruit yield, parthenocarpy, and desired quality from the cultivars remains a challenge for Musa crossbreeding, which started about one century ago in Trinidad. The success of Musa crossbreeding depends on the production of true hybrid seeds in a crop known for its high levels of female sterility, particularly among polyploid cultivars. All banana export cultivars grown today are, however, selections from somatic mutants of the group Cavendish and have a very narrow genetic base, while smallholders in sub-Saharan Africa, tropical Asia and Latin America use some bred-hybrids (mostly cooking types). Musa improvement goals need to shift to address emerging threats because of the changing climate. Innovative cell and molecular biology tools have the potential to enhance the pace and efficiency of genetic improvement in Musa. Micro-propagation has been successful for high throughput of clean planting materials while in vitro seed germination assists in obtaining seedlings after inter-specific and across ploidy hybridization. Flow cytometry protocols are used for checking ploidy among genebank accessions and breeding materials. DNA markers, the genetic maps based on them, and the recent sequencing of the banana genome offer means for gaining more insights in the genetics of the crops and to identifying genes that could lead to accelerating Musa betterment. Likewise, DNA fingerprinting has been useful to characterize Musa diversity. Genetic engineering provides a complementary tool to Musa breeders who can introduce today transgenes that may confer resistance to bacteria, fungi and nematodes, or enhance pro-vitamin A fruit content. In spite of recent advances, the genetic improvement of Musa depends on a few crossbreeding programs (based in Brazil, Cameroon, Côte d'Ivoire, Guadeloupe, Honduras, India, Nigeria, Tanzania and Uganda) or a handful of genetic engineering endeavors (Australia, Belgium, India, Kenya, Malaysia and Uganda). Development investors (namely international aid and philanthropy) should therefore increase their funding to genetically enhance this crop that ranks among the 10-top staple foods of the developing world.